Kecerdasan Buatan Dalam Otomatisasi Pengujian Perangkat Lunak E-Commerce - Abie Fathu Rachman; Dendy Ahmad Ridwan; Kartono; Soleh Damarudin; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The main aim of this paper was to review how artificial intelligence works in software test automation. When it comes to software engineering, artificial intelligence (AI) has had a significant influence, and software testing is no exception. With artificial intelligence (AI), the goal of software test automation may be closer than ever before. To some extent, the paradigm has changed during the previous two decades]. Everything about the testing process has been a positive experience, starting with manual testing and progressing to automated testing, where Selenium is acknowledged to be one of the best test automation tools. As a result, in today's high-speed IT landscape software testing must come up with fresh testing approaches that are based on solid research. The emergence of AI-based testing has been very beneficial for this aim. A computer's ability to learn without human involvement may be fully simulated by AI algorithms and machine learning (ML). While AI and ML entail the construction of distinct and unique algorithms to access data and learn from it by identifying patterns to make conclusions, these predictions are intended to be employed in software testing to their full potential.